Parasite Assemblage, Prevalence and Zoonotic Potential in the Spotfin Bigeye Priacanthus tayenus from the South China Sea, East-Coast Peninsular Malaysia - Suhairi Mazelan; Faizah Shaharom; Wahidah Wahab; Muhammad Hafiz Borkhanuddin; Nor Asma Husna Mohammed Yusoff; Sharifah Raina Manaf; Norazizah Kemat; Nora Faten Afifah Mohamad; Ruhil Hayati Hamdan; Melissa B. Martin; Ahmad Shuhaimi Draman; Shengkang Li; Yenni Putri Sari; Mohd Ihwan Zakariah; Mazlan Abd Ghaffar; Khor Waiho (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Marine capture fisheries are central to food security in Southeast Asia, yet commercially harvested fish can harbour parasites of ecological and public-health significance. Objective: To characterise the parasite assemblage of the spotfin bigeye Priacanthus tayenus from the South China Sea off east-coast Peninsular Malaysia (Terengganu) and to benchmark the zoonotic and quality-relevant taxa against seafood-safety standards. Methods: Fifty wild-caught fish (total length 13.3 ± 2.1 cm) were examined by standard parasitological post-mortem; parasites were slide-mounted and identified morphologically. Infection and diversity indices, a chi-square test, Spearman correlations, a Welch t-test and principal component analysis (PCA) were computed; α = 0.05. Results: A total of 365 specimens of ten taxa (six ectoparasite and four endoparasite groups) were recovered. The anisakid nematode Hysterothylacium sp. dominated (177 specimens; 48.5% relative dominance; 60% prevalence) and Didymozoon sp.1 was most prevalent (62%). Prevalence differed among taxa (χ² = 130.47, df = 9, p < 0.001) and correlated strongly with abundance (ρ = 0.939, p < 0.001). Diversity was moderate (Shannon H' = 1.327; Berger–Parker d = 0.485) and PC1 explained 94.0% of the infection-parameter variance. Conclusion: Visible zoonotic anisakid larvae and trypanorhynch cestodes conflict with the visible-parasite provisions of EU Regulation (EC) 853/2004, underscoring the need for candling, evisceration, freezing and routine surveillance to safeguard seafood safety and food security in this fishery.